Production of whey protein nanofiber as a carrier for copper entrapment. (July 2022) - Zhong, Jie; Jia, Jinxia; Lyu, Quanjun; Chen, Gaiyun; Fu, Sanxian
Abstract: Novel electrospun fibers from aqueous whey protein solution with and without a carrier polymer have been developed and characterized, exploring the ability of those fibers to carry nutrients that are considered attractive. In this study, whey protein concentrate (WPC) solution electrospun into nanofibers in conjunction with (1% w /w in solution) and without a spinnable polymer, polyethylene oxide (PEO), for carrying copper. The electrospun fibers were successfully produced from WPC/copper and a PEO/WPC/copper polymer solution under the applied voltage of 15–23 kV, when the copper concentration was relatively low. The applied voltage has no significant effect on the size of the fibers produced by WPC/copper and PEO/WPC/copper polymer systems ( p > 0.05). The copper concentration in WPC/copper and the PEO/WPC/copper polymer solution significantly affect the viscosity of the solution and the size of the fiber ( p < 0.05), but it has no observable change on the morphology of the fiber. The addition of PEO in the polymer solution slightly increases the solution viscosity, but the fiber of the polymer solution with PEO was 100–400times smaller than that without PEO. Micron fibers prepared by WPC polymer solution and nanofibers prepared by PEO/WPC polymer solution successfully carried copper. Highlights: Whey protein electrospun fiber had the potential to carry the copper ion. Copper content in the polymer solution appeared to significantly influence the fiber morphology. Change in fiber morphology with the addition of a small amount of PEO.